The identification of a SARs-CoV2 S2 protein derived peptide with super-antigen-like stimulatory properties on T-cells - Thai Hien Tu; Fatima Ezzahra Bennani; Nasser Masroori; Chen Liu; Atena Nemati; Nicholas Rozza; Amichai Meir Grunbaum; Richard Kremer; Catalin Milhalcioiu; Denis-Claude Roy; Christopher E. Rudd (Communications Biology)
Abstract Severe COVID-19 can trigger a cytokine storm, leading to acute respiratory distress syndrome (ARDS) with similarities to superantigen-induced toxic shock syndrome. An outstanding question is whether SARS-CoV-2 protein sequences can directly induce inflammatory responses. In this study, we identify a region in the SARS-CoV-2 S2 spike protein with sequence homology to bacterial super-antigens (termed P3). Computational modeling predicts P3 binding to sites on MHC class I/II and the TCR that partially overlap with sites for the binding of staphylococcal enterotoxins B and H. Like SEB and SEH derived peptides, P3 stimulated 25–40% of human CD4+ and CD8 + T-cells, increasing IFN-γ and granzyme B production. viSNE and SPADE profiling identified overlapping and distinct IFN-γ+ and GZMB+ subsets. The super-antigenic properties of P3 were further evident by its selective expansion of T-cells expressing specific TCR Vα and Vβ chain repertoires. In vivo experiments in mice revealed that the administration of P3 led to a significant upregulation of proinflammatory cytokines IL-1β, IL-6, and TNF-α. While the clinical significance of P3 in COVID-19 remains unclear, its homology to other mammalian proteins suggests a potential role for this peptide family in human inflammation and autoimmunity.